Pitfalls in Rhinoplasty: Avoiding Mismatch Between Anatomy, Patient Expectation and Mastery of The Surgeon - Susanto, Imam (Jurnal Plastik Rekonstruksi, 2012)
Background: Aesthetic surgery is a component of Plastic Surgery which deals with a “normal” person with neither disease nor disfigurement. They seek surgery to enhance appearance, which is expected to boost confidence level and performance. Because aesthetic patient come with no physical deformity, their expectation for perfection is high. As plastic surgeons, we must be aware of the pitfalls in our works, how much can we deliver the expectations of patients as suited to our knowledge and our capability in mastering surgical technique including the implementation of new techniques combined with technology. Our awareness throughout each surgery, and the obsession for perfection must measure up to what the patient desire. Patients and Method: A review of 3 augmentation rhinoplasty patient cases who come to my private practice between 2006-2012 with concern of postoperative results is presented, prior previous surgeries were done either by author or other surgeons. Result: All patients received surgical counseling and scheduled correctional surgeries, nearly all patient accepted the final results and were satisfied. Summary: Pitfalls are common in aesthetic surgeries. To prevent this, we must be aware all aspects involved starting from the first consultation with patient, carefully assess the anatomy and anomaly of each case, master the surgical techniques used, and careful when implementing new techniques. Finally, have the wisdom to say ‘no’ to patients who are not good candidates for aesthetic surgery.